XPS studies on the Cu(I,II)-polyampholyte heterogeneous catalyst: An insight into its structure and mechanism - Lazaro Martinez, Juan Manuel (2011)
A complex between Cu(II) and a polyampholyte synthesized from methacrylic acid, imidazole and ethyleneglycol diglycidyl ether was used as a heterogeneous catalyst for hydrogen peroxide activation and degradation of chlorophenols. The material was characterized by XPS and by measurements of the zeta potential. The isoelectric point determined experimentally was 8.0, differing from that obtained by titration (6.4), which indicated the presence of fixed positive charges in disubstituted imidazole units. The XPS N 1s signal for pyridinic nitrogen in the imidazole units, and the O 1s signals from the carbonyl, hydroxyl and carboxylate groups shifted to higher binding energies after copper uptake, proving the chemical nature of Cu(II) adsorption on the polyampholyte. The XPS spectrum of the complex showed a Cu 2p3/2 peak at 934.7 eV and the characteristic shake-up satellite of Cu(II). When the complex was used as a heterogeneous catalyst for H2O2 activation, Cu(I) was proved to be a probable intermediate species and contributed to elucidate the mechanism. The Auger CuLMM spectrum supports the presence of Cu(I) with a kinetic energy value of 914.8 eV. The complex was applied in the oxidation of chlorinated phenols in aqueous solution at room temperature without any loss in efficiency. © 2011 Elsevier B.V. All rights reserved.